impact of flexible working hours on employee work life balance and job satisfaction - ARIYE VIVIAN BAKORU LENIA (My University, 2024)
This study explores the impact of flexible working hours on employee work-life balance and job satisfaction within Coca-Cola Uganda, addressing a significant organizational challenge: the need to balance work demands with personal needs in an evolving work environment. The research was motivated by the increasing global shift toward flexible work arrangements, accelerated by technological advancements and the COVID-19 pandemic, and the scarcity of research on these practices in nonWestern organizational contexts. Guided by the Job Demands-Resources (JD-R) model and the Work-Life Border Theory, the study adopted a qualitative research design to analyse the lived experiences of employees at Coca-Cola Uganda. Data were collected through semi-structured interviews and focus group discussions with employees across different demographic groups, including age, gender, and job roles. The study’s primary objectives were to examine how flexible working hours’ influence employees’ work-life balance, assess the relationship between flexible working hours and job satisfaction, and analyse the role of demographic factors in shaping these outcomes. The findings reveal that flexible working hours significantly enhance employees’ worklife balance by reducing conflicts between work and personal responsibilities. Employees with access to flexible working arrangements reported greater control over their schedules, leading to reduced stress levels and improved well-being. According to the research, a high degree of positive correlation has been noted between flexitime and job satisfaction. This is because workers are motivated to be more loyal to their organizations and increase productivity owing to the freedom and assistance they receive from their employers. On the other hand, there were some problems such as poor team cohesion and differences of influence of flexitime on various types of jobs identified in the research too. Demographic factors, particularly age and gender, influenced employees’ perceptions and experiences of flexible working hours, with younger employees and women benefitting more from these arrangements due to their unique personal and familial responsibilities. vii Overall, the study concludes that flexible working hours offer substantial benefits to employee well-being and job satisfaction at Coca-Cola Uganda. Nevertheless, for such policies to be effective, organizations must address implementation challenges, ensuring that flexible work arrangements are inclusive and adapted to the diverse needs of their workforce. The study’s findings offer valuable insights for Coca-Cola Uganda’s management and HR professionals, guiding the development of more effective workplace policies that foster employee satisfaction and organizational success.